Bioceramics for osteochondral tissue engineering and regeneration - Pina, Sandra Cristina Almeida (2018)
Considerable advances in tissue engineering and regeneration have been accomplished over the last decade. Bioceramics have been developed to repair, reconstruct, and substitute diseased parts of the body and to promote tissue healing as an alternative to metallic implants. Applications embrace hip, knee, and ligament repair and replacement, maxillofacial reconstruction and augmentation, spinal fusion, bone filler, and repair of periodontal diseases. Bioceramics are well-known for their superior wear resistance, high stiffness, resistance to oxidation, and low coefficient of friction. These specially designed biomaterials are grouped in natural bioceramics (e.g., coral-derived apatites), and synthetic bioceramics, namely bioinert ceramics (e.g., alumina and zirconia), bioactive glasses and glass ceramics, and bioresorbable calcium phosphates-based materials. Physicochemical, mechanical, and biological properties, as well as bioceramics applications in diverse fields of tissue engineering are presented herein. Ongoing clinical trials using bioceramics in osteochondral tissue are also considered. Based on the stringent requirements for clinical applications, prospects for the development of advanced functional bioceramics for tissue engineering are highlighted for the future.